Postoperative outcomes of preoperative exercise training in patients with operable non-small cell lung cancer: a systematic review and meta-analysis - Li, Cuifang; Meng, Haidan; Wei, Ye; Liang, Yugan; Xu, Yangqian; Huang, Xiaomeng; Liang, Weiming; Quan, Jieru; Wu, Shanguang; Wei, Xueyan (Frontiers in Oncology, 2025)
IntroductionThis meta-analysis was designed to compare the outcomes of preoperative exercise training versus no preoperative exercise for lung cancer patients scheduled for lung resection.Materials and methodsFour databases (Medline, Embase, Web of Science, and CENTRAL) were searched for randomized controlled trials (RCTs) comparing preoperative exercise training versus no preoperative exercise for lung cancer patients scheduled for lung resection. The primary outcomes were postoperative complications and postoperative length of hospital stay. The secondary outcomes included post-intervention pulmonary function, severe postoperative complications, postoperative 30-day mortality, postoperative duration of chest tube drainage, post-intervention dyspnea, and post-intervention health-related quality of life (HRQoL).ResultsA total of 16 RCTs with 1,022 individuals were included in this meta-analysis. Compared with no preoperative exercise, preoperative exercise training significantly reduced the postoperative complications (OR = 0.33, 95%CI: 0.24 to 0.46, P < 0.0001) and postoperative length of hospital stay (95%CI: −3.11 to −1.40, P < 0.0001). In addition, preoperative exercise training significantly improved forced expiratory volume in 1 s (FEV1%) of predicted norm values (95%CI: 5.30 to 8.10, P < 0.0001), forced vital capacity (FVC%) of predicted norm values (95%CI: 1.90 to 4.23, P < 0.0001), peak expiratory flow (PEF) (95%CI: 12.44 to 60.93, P = 0.003), and peak oxygen uptake (VO2peak) (95%CI: 2.41 to 4.17, P < 0.0001), while reducing severe postoperative complications (OR = 0.35, 95%CI: 0.21 to 0.56, P < 0.0001) and post-intervention dyspnea (95%CI: −0.61 to 0.04, P = 0.02). There was no significant difference between the two groups regarding FEV1, FVC, carbon monoxide diffusing capacity (DLCO), six-minute walk distance (6MWD), postoperative 30-day mortality, postoperative chest tube drainage time, and post-intervention HRQoL.ConclusionsThis meta-analysis indicated that preoperative exercise training was effective for lung cancer patients scheduled for lung resection, potentially reducing postoperative complications and hospital stay duration, while improving post-intervention pulmonary function and exercise capacity.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024607156.